Obesity as a Risk and Severity Factor in Rheumatic Diseases (Autoimmune Chronic Inflammatory Diseases) - Gremese, Elisa; Tolusso, Barbara; Gigante, Maria Rita; Ferraccioli, Gianfranco (Frontiers in Immunology, 2014)
The growing body of evidence recognizing the adipose tissue as an active endocrine organ secreting bioactive mediators involved in metabolic and inflammatory disorders, together with the global epidemic of overweight and obesity, rise obesity as a hot topic of current research. The chronic state of low grade inflammation present in the obese condition and the multiple pleiotropic effects of adipokines on the immune system has been implicated in the pathogenesis of several inflammatory conditions including rheumatic autoimmune and inflammatory diseases. We will discuss the main relevant evidences on the role of the adipose tissue on immune and inflammatory networks and the more recent evidences regarding the effects of obesity on the incidence and outcomes of the major autoimmune chronic inflammatory diseases.